SAR Distribution with Different Water Bolus Shapes for Hyperthermia Breast Cancer Treatment - Mazlina, Mansor Hassan; Kasumawati, Lias; Norlida, Buniyamin; Mohamad Zulkarnaen, Ahmad Narihan; Bibi Sarpinah, Sheikh Naimullah; Hazrul, Mohamad Basri; Syah, Alam (Semarak Ilmu Publishing, 2025)
Hyperthermia is an alternative treatment for breast cancer and involves a high temperature of 41℃ to 45℃ to heat malignant tissues into necrotic tissues. A 915MHz and 2450MHz rectangular microstrip patch inset feed line antenna is designed with SEMCAD X 14.8.4 software simulator. The non-invasive antenna is used in the hyperthermia treatment to destroy the malignant tissues. However, hyperthermia creates unwanted hotspots and causes skin burn problems. Therefore, a water bolus is designed with several shapes coupled with an antenna to cool the treated areas. In this research, the hyperthermia treatment is applied to the three different sizes of malignant tissues labelled as T1, T2 and T3 with diameters of 15mm, 34mm and 59mm respectively. The sizes are based on the data from the mammogram image analysis received from the hospital. The observation is made for the antenna with and without water bolus. A deionized and distilled water bolus is designed with rectangular, circular and sphere shapes and integrated with the antenna. The applicator’s performance is analysed. The simulation results show that the water bolus helps to reduce unwanted hotspots, increase the focus position distance and is able to control delivered heat more uniformly to surrounding malignant tissues. The sphere shape shows better SAR performance than circular and rectangular. Moreover, the procedure can be done in a much shorter time using a sphere shape than two other shapes.